Chatbot assisted inquiry and ticket booking system for cinema - Khiu, Zhen Hung (2020)
Chatting Robot (Chatbot) has gradually played an important role in our daily life. It is widely used in daily life due to high response rate and ability to handle multiple users at the same time. Besides, implementation of chatbot in the entertainment industry allows the customers to clear their doubt anytime and anywhere as long as there is an internet connection. However, the chatbot-based inquiry and ticket booking system for cinema is not developed because there is no centralized database that contains the cinema and movie details, which causes the customers need to obtain the info manually. Besides, the existing ticket booking system is also not user-friendly due to the complex and non-standardized interface. Thus, this project aims to develop a chatbot-based inquiry and ticket booking system for cinema to eliminate complex steps and provide convenience to them by booking tickets using quick reply button. For this project, the main focuses are developing chatbot for inquiry related to FAQ of cinema information with English and Bahasa Malaysia translation as well as ticket booking using natural language. Therefore, waterfall model is used as the methodology for the development of the chatbot-based cinema inquiry and ticket booking system, organizing database for the details of the cinemas and movies, generating knowledge-based to clear the user doubt and booking tickets. The accuracy of the chatbot to provide relevant answers is discussed in this project. In conclusion, this project avoids the customer to go through the complex step of getting the desired answer and booking a ticket for a movie.